Viabilidade econômica da venda de energia elétrica em co-geração sob condições de risco: um estudo de caso - Fodra, Marcelo [UNESP] (Universidade Estadual Paulista (Unesp), 2012)
A disponibilidade de energia elétrica, em quantidades suficientes e a preços competitivos, é um fator decisivo para o desenvolvimento econômico. A venda de energia elétrica excedente, produzida em um sistema de co-geração, pode ser vista como uma alternativa para a criação de uma fonte adicional de receita para as empresas do setor sucroalcooleiro, bem como, contribuir para a complementação da matriz elétrica brasileira com fontes renováveis. Este trabalho teve como objetivo avaliar a viabilidade econômica da realização de investimentos para a implantação de uma central de co-geração de energia elétrica, movida a bagaço de cana-de-açúcar, com a finalidade de venda de energia elétrica cogerada excedente a preços de mercado. A empresa objeto deste estudo foi uma usina sucroalcooleira, localizada no Estado de São Paulo. Utilizou-se o método do estudo de caso para a avaliando-se o potencial do investimento sob a ótica do VPL, Payback e TIR, complementando-se os resultados com o Resultado Contábil. Foram criados três cenários alternativos para refletir o grau de risco em cada tipo de situação estudada: mais provável, otimista e pessimista, cada qual com suas premissas. A inserção dos elementos de risco do projeto em cada cenário foi realizada com emprego de Simulações de Monte Carlo. A avaliação pelo VPL indicou que no cenário pessimista ocorreram aproximadamente 80% de probabilidades de obtenção de VPL positivo. No cenário mais provável e no otimista, estas probabilidades foram maiores...

The availability of the electrical energy, in sufficient quantities and the competitive prices is a crucial factor to the economic development. The sale of the excess electrical energy, produced in a system of cogeneration can be seen as an alternative to the creation of an additional source of revenues for power plants of alcohol sector, besides contributing to the complementation of the Brazilian electrical headquarter with renewable sources. The task has had the aim of evaluating the economic feasibility of the investment achievement to the implementation of a cogeneration electrical central, moved by the excess of bagasse cane sugar focusing on the excess electrical energy sale to prices of the market. The power plant which has been studies was the alcohol plant, located in the state of São Paulo. It has been used the method of study of case, evaluating the potential of the investment under the viewpoint of the Net Present Value (NPV), Payback and Internal Rate of Return (IRR), complementing the results of the Accounting Results (AC). It has been created three alternative scenarios to reflect the level of the risk of every studied situation. The most likely, optimistic and pessimistic, each one with its assumptions. The insertion of the elements of risk of the project in each scenario has been made with the use of Monte Carlo Simulations. The evaluation by NPV has shown that in the pessimist scenario has occurred approximately 80 per cent of the probabilities of the obtention of the positive NPV. On the most likely scenario and also the optimistic, these probabilities have been more than 90 per cent. The analysis on the Payback has shown that the liquid flow discounted of the cash of the product allows the recovery of the invested capital in approximately 5.26 years in the pessimist scenario. In the most likely scenario has... (Complete abstract click electronic access below)
Keywords: Viabilidade economica; Energia eletrica e calor - Cogeração; Energia elétrica - Comercialização; Bagaço de cana; Bagasse; Energy conservation